Kinerja Arsitektur Interoperabilitas Menggunakan Government Service Bus (GSB) dan Peer to Peer (P2P) - Eko Wiyatnanto; Arief Indriarto Haris (Ultimatics : Jurnal Teknik Informatika, 2021)
The role of interoperability architecture is one of the solutions to data redundancy problems and data differences that cause the level of data accuracy to be low. However, the performance of the interoperability architecture needs to be evaluated as an effort to improve the quality of the application itself. This study aims to evaluate the interoperability architecture between architectures using the Government Service Bus (GSB) and Peer to Peer (P2P), through several tests, namely load testing and stress testing. Load testing and stress testing aim to measure the speed and resilience of an application by sending requests and measuring the response of the application. The difference is that in load testing, testing is carried out with certain load conditions, while in stress testing, testing is carried out under extreme conditions. Testing load testing, determining the load condition with a multiple of the number of users 100 to 500, with the JMeter tools. In stress testing, testing is carried out with a total of 1000 users, with the Loader.io tools. The results of the load testing show that the average access time for GSB is smaller than P2P, with an average of 2ms to 309ms and a request error rate of 0%. The results of stress testing show that the GSB architecture is faster than the P2P architecture with an average difference in access time of 2957ms, a difference in throughput of 1.5 request/second, but GSB has a higher request error rate than P2P with a difference of 16.05%. In general conditions with certain loads, the GSB architecture has superior performance, this can be seen from the access time and request errors. Meanwhile, in extreme conditions the GSB architecture experiences a decline in performance, this can be seen from a larger request error rate when handling very large requests.